Alcohol and pregnancy: Effects on maternal care, HPA axis function, and hippocampal neurogenesis in adult females. (July 2015) - Workman, Joanna L.; Raineki, Charlis; Weinberg, Joanne; Galea, Liisa A.M.
Highlights: Chronic alcohol consumption during pregnancy reduced maternal care. Prior alcohol consumption increased HPA axis function in nulliparous females only. Primiparity reduced neurogenesis and altered development of immature neurons. Chronic alcohol did not alter neurogenesis after a period of abstinence. Summary: Chronic alcohol consumption negatively affects health, and has additional consequences if consumption occurs during pregnancy as prenatal alcohol exposure adversely affects offspring development. While much is known on the effects of prenatal alcohol exposure in offspring less is known about effects of alcohol in dams. Here, we examine whether chronic alcohol consumption during gestation alters maternal behavior, hippocampal neurogenesis and HPA axis activity in late postpartum female rats compared with nulliparous rats. Rats were assigned to alcohol, pair-fed or ad libitum control treatment groups for 21 days (for pregnant rats, this occurred gestation days 1–21). Maternal behavior was assessed throughout the postpartum period. Twenty-one days after alcohol exposure, we assessed doublecortin (DCX) (an endogenous protein expressed in immature neurons) expression in the dorsal and ventral hippocampus and HPA axis activity. Alcohol consumption during pregnancy reduced nursing and increased self-directed and negative behaviors, but spared licking and grooming behavior. Alcohol consumption increased corticosterone and adrenal mass only in nulliparous females. Surprisingly, alcohol consumption did not alter DCX-expressing cell density. However, postpartum females had fewer DCX-expressing cells (and of these cells more immature proliferating cells but fewer postmitotic cells) than nulliparous females. Collectively, these data suggest that alcohol consumption during pregnancy disrupts maternal care without affecting HPA function or neurogenesis in dams. Conversely, alcohol altered HPA function in nulliparous females only, suggesting that reproductive experience buffers the long-term effects of alcohol on the HPA axis.